"Playing on Timbrels": the margins of the Rutland Psalter. Issue 1 (2nd January 2016) - Chunko-Dominguez, Betsy
Abstract: This article explores the relationship between the marginal imagery and text of the Psalms within the thirteenth-century Rutland Psalter. It is argued that certain marginal images, which appear predominantly secular in nature, interact with and illuminate the text of the Psalms in surprising ways. These marginal figures evince a dynamic creative process in which a secular body of illuminators used words and phrases on the page to initiate playful and often quasi-literate pictorial responses. Furthermore, in at least one instance the margins of the Rutland Psalter interact with not just the words of the Psalm but the meaning behind them. The bas-de-page figures accompanying the miniature of Jacob's Dream of the Ladder at the start of Psalm 80 encourage the viewer to contemplate the text of the Psalms, much like the textual glosses stemming from the writings of St. Jerome. Ultimately, this article suggests that the margins were, at their time of creation, a novel way of reinforcing the text for a lay viewer. The very puzzle of encountering an esoteric image could, as a mental exercise for the lay viewer, heighten his or her personal engagement with the page.